2015
DOI: 10.1080/02678292.2015.1015180
|View full text |Cite
|
Sign up to set email alerts
|

Memory effects in chiral nematic liquid crystals doped with functionalised single-walled carbon nanotubes

Abstract: Octadecylamine-functionalised single-walled carbon nanotubes (SWCNTs) were dispersed into nematic liquid crystals (LCs) doped with chiral molecules. The collective orientation of nematic LC molecules in helical layers was manipulated by varying dopant concentration. Highly anisotropic nature of SWCNTs enhanced the anisotropy of the LC as confirmed by polarised fluorescence spectroscopy. The π-π interaction of SWCNTs present in the planar alignment layers and twisted nematic LC molecules affects the molecular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…This dependence for the whole range of the studied temperatures correlates with the temperature dependence of the τ -1 -value. 4. It has been shown that the conductivity of the samples in both homeotropic and planar orientations of molecules changes according to the power law on the concentration of molecules up to the impurity concentration 1 wt.%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This dependence for the whole range of the studied temperatures correlates with the temperature dependence of the τ -1 -value. 4. It has been shown that the conductivity of the samples in both homeotropic and planar orientations of molecules changes according to the power law on the concentration of molecules up to the impurity concentration 1 wt.%.…”
Section: Discussionmentioning
confidence: 99%
“…It is certainly one of the triumphal accords of practical application of LC. In further studies of the LC properties, much of the scientific problems are based on the expansion of the LC functional properties due to the introduction of impurities of different types in them [1][2][3][4][5][6][7]. From our viewpoint, the capabilities of LC-based devices can be greatly expanded, if the impurities will absorb light in the spectral range visible for human eyes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Феррохолестерики привлекательны открывающейся в них возможностью посредством слабых внешних магнитных полей изменять спиральность образуемой структуры и, тем самым, легко модулировать спектральный состав отраженного света. Теоретические и экспериментальные исследования физических явлений в геликоидальных ФМ ЖК вызывают в последние годы большой научный интерес [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionunclassified
“…sp 2 hybridized conjugation remains unaltered. Furthermore, these methods have also been proven efficient and economical, [1][2][3]6,8,9,[11][12][13][14][15][16][17]19,23,25,28,30,32,34,37,39,44,45,47,49,55 hence preferred. Mechanical dispersion methods involve stirring, sonication and calendaring.…”
mentioning
confidence: 99%